Dominant-negative constructs of human 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 and -4: effect on the expression of endogenous 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase mRNA - Minchenko, D.O.; Bobarykina, A.Y.; Ratushna, O.O.; Marunych, R.Y.; Tsuchihara, K.; Moenner, M.; Caro, J.; Esumi, H.; Minchenko, O.H. (Біотехнологія, 2008)
Expression of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB), a key regulatory enzyme of glycolysis, is significantly increased in different malignant tumors provides a potential mechanism of enhanced glycolysis and cancer cell proliferation. We created dominant-negative constructs of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 and -4 (dnPFKFB-3 and dnPFKFB-4) cDNA for suppression of strongly enhanced expression endogenous PFKFB-3 and PFKFB-4. We introduce point mutation in ATP-binding domain of 6-phosphofructo-2-kinase part of PFKFB-3 as well as PFKFB-4 cDNA for suppression of 6-phosphofructo-2-kinase activity in the products of dnPFKFB-3 and dnPFKFB-4 expression. Cancer cells were stable transfected with these dominant-negative constructs for suppression of endogenous PFKFB-3 and PFKFB-4 expression and cell proliferation. We have shown that PFKFB-3 expression in pancreatic cancer cell line Panc1, stable transfected by dnPFKFB-3, was significantly reduced in normal as well as in hypoxic conditions. Pancreatic cancer cells proliferation, stable transfected by dnPFKFB-3 or dnPFKFB-4, was also reduced. Results of this investigation demonstrate possibility to apply the dominant-negative constructs of PFKFB-3 and PFKFB-4 for suppression of glycolysis and tumor cells proliferation via reduction of endogenous PFKFB expression.